Los Cronistas oficiales de Indias. De López de Velasco a Céspedes del Castillo - Cuesta Domingo, Mariano (Revista Complutense de Historia de América, 2008)
State interest in the government of the Spanish American Kingdoms and other overseas possessions of Spain, and in the development of relations with Latin American countries, led the Spanish Crown to create an official position dedicated to the history of America. It was the job of the holder of this position to provide the necessary information to enable government departments to better inform their administrative and executive duties. This article shows how spontaneous historical explanations developed into chronicles and official history, and offers comments on some of the historians who have been appointed to fulfill that task.